William Blake and the Visionary Law - Mauger, Matthew. author. aut Link
XIII, 231 p. 12 illus.
Keywords: This book examines the difficult relationship between individual intellectual freedom and the legal structures which govern human societies in William Blake’s works, showing that this tension carries a political urgency that has not yet been recognised by scholars in the field. In doing so, it offers a new approach to Blake’s corpus that builds on the literary and cultural historical work of recent decades. Blake’s pronouncements about law may often sound biblical in tone; but this book argues that they directly address (and are informed by) eighteenth-century legal debates concerning the origin of the English common law, the autonomy of the judicature, the increasing legislative role of Parliament, and the emergence of the notions of constitutionalism and natural rights. Through a study of his illuminated books, manuscript works, notebook drafts and annotations, this study considers Blake’s understanding that law is both integral to humanity itself and a core component of its potential fulfilment of the ‘Human Form Divine’. Matthew Mauger is Senior Lecturer in English at Queen Mary University of London, UK. His research focuses on the intellectual, literary and commercial life of London in the eighteenth century, with a particular interest in how the administrative frameworks associated with the city – civil, legal, political, financial – provide contexts for literary expression. He is co-author of Stealing Books in Eighteenth-Century London (2016) and of Empire of Tea: The Asian Leaf that Conquered the World (2015).